The seamy side of civilization: Fashion in a meat market setting - K. O. Gusarova (Шаги)
The article considers the wholesale meat market as a persistent background for verbal and visual fashion imagery. This setting is inherently contradictory, as it combines the features of two key sites of industrial modernity, which tend to be seen as unconnected, if not mutually opposed to each other. On the one hand, the meat market, where animal carcasses can be flayed and carved into pieces, bears similarity to the abattoir — a marginal site which in the nineteenth century was removed from Western urban centers for hygienic and moral reasons, yet proved central for shaping modern production technologies and visual regimes. On the other hand, as a place of commerce, the meat market shares some characteristics with a shop window that transforms various materials into commodities and serves as a screen onto which the desires of consumer society are projected. The article focuses on representations of the Parisian central food market, Les Halles, and similar venues situated in the suburbs of Paris and other French cities. The case studies under examination are Emile Zola’s 1873 novel The Belly of Paris; Guy Bourdin’s photographs set in Les Halles and intended for the February 1955 issue of Vogue Paris; and Dora Kallmus 1940–1950s photographic series taken in Parisian abattoirs and meat markets. In all three instances, the meat market becomes both the locus and the object of critical reflection, touching upon such topics as aesthetics and the appeal of commodities, physical vulnerability and mortality, the responsibility of the artist and the audience. While only Bourdin’s photographs feature a literal fashionable display set in a meat market, both Zola and Kallmus draw upon fashion imagery to make a point about the various ways flesh can be commodified.